Parameter Count and Pass@k Performance in Open-Source Code Models on LiveCodeBench - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: What is the correlation between parameter count and pass@k scores for open-source code models across varying difficulty levels in the LiveCodeBench dataset. 16 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.1/10. This report is a machine-generated literature synthesi
Machine-generated literature synthesis.